Managing Stroke Rehabilitation in Elderly - Cipto, Cipto; Wahyudi, Teguh; Normawati, Ajeng Titah (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2023)
The world's elderly population is predicted to triple every year, and have complex consequences such as the incidence of non-communicable diseases, one of which is stroke. Stroke is a disease of impaired brain function that is a global health problem. As many as 2.5% of the 500 thousand stroke sufferers experience disability and even mortality in Asian countries, especially Indonesia. The study describes a rehabilitation program for the stroke elderly with a family approach. Three elderly stroke survivors were given passive and active range of motion exercises in the extremities by their families accompanied by nurses for 10 consecutive days. The results were obtained that all three elderly experienced an increase in muscle strength in part of their extremities at one rate better. From this study, it can be seen that rehabilitation with a family approach can be used as an alternative to improve the mobility ability of the elderly after stroke at home